Perceived Brand Globalness and Localness: A Bibliometric Analysis - Jadach, Robert; Pluta-Olearnik, Mirosława (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The purpose of the article is to establish the current state of research on the perceived brand globalness / localness (PBG / PBL) dichotomy. It analyses and assesses the changes in the research problems and identifies the areas upon which PBG / PBL research is currently focused. Research Design & Methods: The research method used in the article is bibliometric analysis, supplemented by content analysis of literature selected from the Scopus database. A four-step procedure was used to collect data and conduct bibliometric analyses: stage 1 – searching and identifying primary literature, stage 2 – review of the literature (screening), stage 3 – data export, stage 4 – bibliometric analysis supplemented by a content analysis of the literature. In addition, a co-occurrence analysis of keywords was carried out using VOSviewer. Findings: The research on PBG / PBL issues is concentrated in five main areas: 1) brand value signaling, 2) PBG / PBL interaction, 3) PBG impact on purchase intentions, 4) PBL impact on purchase intentions, and 5) the effect of country of origin/consumer ethnocentrism on consumer preference for foreign (global) vs. domestic (local) brands. The study also examines changing trends in PBG / PBL research. Implications / Recommendations: Recent world events including the COVID-19 pandemic, the Russian invasion of Ukraine and trade wars have slowed globalisation. Since buying behaviour is visibly changing under the influence of socio-economic factors, there is a need for further research to verify consumer preferences vis-à-vis global / local brand positioning. Contribution: The review and analyses performed enrich the existing literature on PBG / PBL, while the findings presented can serve as a starting point for further research.